High-fidelity reservoir simulations of enhanced gas recovery with supercritical CO2. (15th September 2016) - Patel, Milan J.; May, Eric F.; Johns, Michael L.
Abstract: EGR (Enhanced natural gas recovery) with CO2 sequestration offers the prospect of significant environmental and economic benefits by increasing gas recovery while simultaneously sequestering the greenhouse gas. Field-scale deployment is currently limited as the risks of contamination of the produced gas by injected CO2 are poorly understood. Reservoir simulations offer a method to quantify the risk but only if sufficiently accurate. For the first time, finite element simulations are presented for several EGR scenarios that incorporate the most accurate models available for fluid mixture and rock properties. Specifically, the GERG-2008 EOS (equation of state) is utilised to describe the supercritical fluid mixture's density, as are reference correlations linked to the most accurate experimental data available for diffusivity and viscosity. Realistic values for rock dispersivity and tortuosity determined from high-accuracy core-flooding and NMR (nuclear magnetic resonance) experiments were also integrated. The relative impacts of these properties were investigated for a benchmark layered reservoir with a quarter 5-spot well pattern. Recovery efficiency at different CO2 injection rates was also investigated and was determined to be the dominant consideration: a 100-fold rate increase improved recovery from 53% to 69% while CO2 breakthrough time decreased by less than expected. Collectively, these results emphasise the importance of accurate reservoir simulations for EGR. Highlights: GERG-2008 EoS (equation of state) efficiently implemented in simulations of enhanced gas recovery. Measured diffusivity, tortuosity & dispersivity data used in EGR (Enhanced natural gas recovery) reservoir simulations. Sinking of (denser) CO2 beneath resident natural gas can accelerate breakthrough. Injection rate has most effect on CO2 breakthrough and CH4 recovery (small reservoir). In larger reservoirs, accurate tortuosity and D measurements essential to accuracy.